Alternative Sanctions and their Impact on Societal Security: A Field Study in the Directorate of Juveniles Reformatory in Baghdad (Journal of the College of Education for Women, 2023)
Crime is one of the most severe challenges facing States, and strives to find preventive measures, reduce its seriousness, and prevent them; due to developments, crimes have increased, and emerging new patterns of crimes, there is an urgent need to prevent crimes and reduce their effects. Modernizing its punitive system and diverting it to correctional rehabilitative justice to redress the prejudice caused by the crime and rehabilitate the convicted person by using alternative measures to short-term imprisonment. This research emphasizes alternative sanctions' value to minimizing short-term imprisonment penalties and their impact on societal security through several goals like, the negative consequences, justifications, and alternatives applied in Iraq, to identify their impact on societal security. The research was based on the analytical descriptive curriculum and the sample-style social survey. It was based on an intentional sample of (250) Research staff of the Directorate of Juvenile Reformatory in Baghdad to measure the role of alternative sanctions in the correctional aspect, statistically processed through the program (SPSS), one of our most important findings is that (92.33%) of researchers supported that alternative sanctions has a role to reduce overcrowding in correctional schools, and supported (91%) of researchers that they are prohibited from mixing with depositors, and that (90%) of researchers who supported that the application of the penalties would reduce the problems associated with the sentence of imprisonment, i.e., the researchers emphasized the importance of alternative sanctions to minimize the effects of the short-term imprisonment on the convicted person, his family, and his community.